Linking the benefits of project management maturity to project complexity: Insights from a multiple case study. Issue 2 (1st April 2014) - Christoph Albrecht, Jan; Spang, Konrad
Abstract : Purpose: – The purpose of the research presented in this article is to identify potential influences on an organization-specific "ideal" level of project management maturity by adopting a qualitative, exploratory approach. Design/methodology/approach: – In this paper, the results of a multiple qualitative case study, which has been conducted within industrial enterprises from automotive industry and energy sector, are presented. The research methods applied within the case research are qualitative guided interview, document analysis and standardized interview (maturity questionnaire). Findings: – The interview data reveal that the complexity of the companies' projects might be a determining factor regarding the "ideal" level of maturity. A comparison of the findings of the case research with a secondary literature review on project complexity showed that particularly those facets of project complexity that affect the interaction of the project participants (project team, client, suppliers) seem to require a certain level of maturity. Originality/value: – The idea of an organization-specific "ideal" level of maturity was raised by the developers of project management maturity models (PMMM). It is of interest for professionals due to efficiency reasons. Research literature in the context of PMMM has so far touched on environmental/circumstantial influences on this ideal maturity level only to a slight degree. The results of the qualitative research presented herein mark a contribution to this research gap and allow for quantitative testing.